2019
DOI: 10.1001/jamanetworkopen.2019.2200
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Population Health in US Academic Medicine

Abstract: This qualitative study describes the emergence of departments of population health at US academic medical centers, including shared areas of focus, opportunities, and challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…As hospitals begin to develop departments of population health (40), they can leverage that growing expertise-in data collection and analysis, in implementation science, in partnering to promote health and wellness outside their walls-to guide their community health improvement programs and widen the lens from patients in the delivery system to residents in the community. In this way, community benefit resources can be deployed more effectively to address important community health priorities, build community and institutional capacity, and lay a foundation for long-term sustainable change.…”
Section: Resultsmentioning
confidence: 99%
“…As hospitals begin to develop departments of population health (40), they can leverage that growing expertise-in data collection and analysis, in implementation science, in partnering to promote health and wellness outside their walls-to guide their community health improvement programs and widen the lens from patients in the delivery system to residents in the community. In this way, community benefit resources can be deployed more effectively to address important community health priorities, build community and institutional capacity, and lay a foundation for long-term sustainable change.…”
Section: Resultsmentioning
confidence: 99%
“…7 Within universities, academic health centers (AHCs) are the natural home for health services/population health research. 2,3 In a recently published analysis of the ways in which US AHCs support multidisciplinary health services research activities, Gourevitch et al 2 identified 15 AHC departments (with "population" as part of the department name) across all US accredited medical schools, each with unique structural characteristics. However, as the results of this survey illustrate, well-defined academic departments are not the only homes for health services/population health investigators.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is increased interest and focus on health services/population health research, and many academic medical centers are now forming formal departments of population health. 2,3 The term population health often refers to the health or determinants of health among a group of patients receiving health care from a health care delivery system or academic institution. The term is also used when referring to the health and determinants of health of persons residing in a particular geographic area or specific community, regardless of their receipt of health care services.…”
Section: Introductionmentioning
confidence: 99%
“…However, population health departments can and must play a critical role to "bridge the worlds of medicine and public health and of delivery system and community." 3…”
Section: Measuring Successmentioning
confidence: 99%
“…Within their regions, outcome measures may include lower premature mortality rates, improved measures of well-being and equity, falling per capita health care investments, along with increased investments in more upstream determinants.For a concrete step, we welcome the authors' interest in organizing a forum for sharing their academic missions, experiences, and emerging ideas and concur that the Interdisciplinary Association for Population Health Science (IAPHS) has a "strong thematic alignment. "3 As former and current IAPHS board members, we are pleased that IAPHS will host a preconference event for the Academic Population Health Leaders Working Group before the IAPHS 2019 annual meeting 8.…”
mentioning
confidence: 99%